Pengaruh Metode Outdoor Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran SBDP Kelas V SDN 30 Palembang - Anggraeni, Oktatia; Wahidy, Achmad; Utami, Sonia Anisah (ALACRITY : Journal of Education, 2024)
This study aims to determine whether the Outdoor Learning method can improve the learning outcomes of SBdP of fifth grade students of SD Negeri 30 Palembang. This research is a type of quantitative research using the experimental method of True Experimental Design in the form of posttest-only control design. The variables of this study consisted of independent variables (X), namely the Outdoor Learning method and the dependent variable (Y), namely student learning outcomes. The population of this study were students of class VB and VC SD Negeri 30 Palembang which amounted to 56 students, the samples taken were class VB students as an experimental class of 28 students taught using the Outdoor Learning method and class VC as a control class of 28 students taught conventionally. In sampling using purposive sampling. The data collection technique used in this study is an art making test, the test is used to improve student learning outcomes in SBdP subjects. Data analysis techniques using t-tests. The results showed the value of tcount = 4.487> ttable = 1.674 and a significant value <0.05 then HO is rejected, which means that there is an effect of the Outdoor Learning method on student learning outcomes in SBdP subjects in grade V SD Negeri 30 Palembang.